Alpha-synuclein oligomerization and dopaminergic degeneration occur synchronously in the brain and colon of MPTP-intoxicated parkinsonian monkeys. (18th January 2020) - Li, Xuran; Yang, Weiwei; Li, Xin; Chen, Min; Liu, Chengwei; Li, Jie; Yu, Shun
Highlights: α-Syn oligomerization occurs in parallel in the brain and colon of MPTP-treated monkeys. α-Syn oligomerization correlates with its phosphorylation in MPTP-treated monkeys. α-Syn phosphorylation is accompanied by alterations in its regulatory enzymes PP2A and PLK2. DAergic degeneration is synchronized in the brain and colon of MPTP-treated monkeys. Altered PLK2 and PP2A activity contribute to α-syn phosphorylation and oligomerization. Abstract: Dopaminergic (DAergic) degeneration and abnormal α-synuclein (α-syn) expression, phosphorylation and aggregation are observed in both the nigrostriatal system (NSS) and enteric nervous system (ENS) of patients with Parkinson's disease (PD). Whether these alterations in α-syn and DAergic neurons occur synchronously in the two nervous systems or follow a process that spreads from the gut to the brain remains a subject of debate. Here, in MPTP-intoxicated cynomolgus monkeys, we showed a parallel DAergic degeneration in the colon as well as in the substantia nigra and striatum (SN/STR), as indicated by reduced expression of tyrosine hydroxylase (TH) and dopamine transporter (DAT). In addition, we observed a simultaneous increase in the concentrations of total, phosphorylated, and oligomeric α-syn in the colon and SN/STR. Moreover, we identified that the above changes in α-syn were associated with an increase in the expression of polo-like kinase 2 (PLK2), an enzyme that promotes α-syn phosphorylation, and a decrease in the activity of protein phosphatase 2A (PP2A), an enzyme that facilitates α-syn dephosphorylation. Because the colonic ENS can be readily analyzed using routine biopsies, the shared pathological features between the colonic ENS and the brain NSS found in this study provide useful information for assessing and understanding the neuropathology in PD patients using colonic biopsies.